A Sustainable Route from Biomass Byproduct Okara to High Content Nitrogen‐Doped Carbon Sheets for Efficient Sodium Ion Batteries. Issue 3 (24th November 2015) - Yang, Tingzhou; Qian, Tao; Wang, Mengfan; Shen, Xiaowei; Xu, Na; Sun, Zhouzhou; Yan, Chenglin
Abstract : A sustainable route from the biomass byproduct okara as a natural nitrogen fertilizer to high‐content N‐doped carbon sheets is demonstrated. The as‐prepared unique structure exhibits high specific capacity (292 mAh g −1 ) and extremely long cycle life (exceeding 2000 cycles). A full battery is devised for the practical use of materials with a flexible/wearable LED screen.